CD123 expression levels in 846 acute leukemia patients based on standardized immunophenotyping. Issue 2 (18th November 2018) - Bras, Anne E.; de Haas, Valerie; van Stigt, Arthur; Jongen‐Lavrencic, Mojca; Beverloo, H. Berna; te Marvelde, Jeroen G.; Zwaan, C. Michel; van Dongen, Jacques J.M.; Leusen, Jeanette H.W.; van der Velden, Vincent H.J.
Abstract : Background: While it is known that CD123 is normally strongly expressed on plasmacytoid dendritic cells and completely absent on nucleated red blood cells, detailed information regarding CD123 expression in acute leukemia is scarce and, if available, hard to compare due to different methodologies. Methods: CD123 expression was evaluated using standardized EuroFlow immunophenotyping in 139 pediatric AML, 316 adult AML, 193 pediatric BCP‐ALL, 69 adult BCP‐ALL, 101 pediatric T‐ALL, and 28 adult T‐ALL patients. Paired diagnosis‐relapse samples were available for 57 AML and 19 BCP‐ALL patients. Leukemic stem cell (LSC) data was available for 32 pediatric AML patients. CD123 expression was evaluated based on mean fluorescence intensity, median fluorescence intensity, and percentage CD123 positive cells. Results: EuroFlow panels were stable over time and between laboratories. CD123 was expressed in the majority of AML and BCP‐ALL patients, but absent in most T‐ALL patients. Within AML, CD123 expression was lower in erythroid/megakaryocytic leukemia, higher in NPM1 mutated and FLT3‐ITD mutated leukemia, and comparable between LSC and leukemic blasts. Within BCP‐ALL, CD123 expression was higher in patients with (high) hyperdiploid karyotypes and the BCR‐ABL fusion gene. Interestingly, CD123 expression was increased in BCP‐ALL relapses while highly variable in AML relapses (compared to CD123 expression at diagnosis). Conclusions: Authors evaluated CD123 expression in a large cohort of acute leukemia patients, based on standardized and reproducible methodology. Our results may facilitate stratification of patients most likely to respond to CD123 targeted therapies and serve as reference for CD123 expression (in health and disease). © 2018 The Authors. Cytometry Part B: Clinical Cytometry published by Wiley Periodicals, Inc. on behalf of International Clinical Cytometry Society.